If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 6(2x + -3) = 4 + -7 Reorder the terms: 3x + 6(-3 + 2x) = 4 + -7 3x + (-3 * 6 + 2x * 6) = 4 + -7 3x + (-18 + 12x) = 4 + -7 Reorder the terms: -18 + 3x + 12x = 4 + -7 Combine like terms: 3x + 12x = 15x -18 + 15x = 4 + -7 Combine like terms: 4 + -7 = -3 -18 + 15x = -3 Solving -18 + 15x = -3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + 15x = -3 + 18 Combine like terms: -18 + 18 = 0 0 + 15x = -3 + 18 15x = -3 + 18 Combine like terms: -3 + 18 = 15 15x = 15 Divide each side by '15'. x = 1 Simplifying x = 1
| 3a^2-a-z-32=0 | | 5x-3+7=4x+3-7 | | y=8x-105 | | 3x+6(2x-y)=4-7x | | 3a^2-a-32=0 | | 5y-22=-15+4y | | 15x=5x | | 9x+15-8x=-2-10 | | 4x=15x | | 9n-8=-20+3n | | 4x=2(6x+16) | | -8(-8x-6)=6(5x+4) | | 4x+14-3x=-5-10 | | -5(x+1)-13=10+2 | | 6x=2(8x+20) | | (2x+4)(x-5)=0 | | 5p=-40-33p | | 15x-29y=429 | | 4x^2-16x+5= | | 4P=7(7P+3) | | 4(3+2x)-3=49 | | x+13x=-40 | | 5y+3=-5 | | 3x^2-9x+27=0 | | 2x-8x+6=-19 | | 4x+8=20x+1 | | 70+20x=350 | | 4x+2=20x+1 | | -3+4x=-1-6x | | 1x+1x+48=3x+5x | | 7x+4/3=2x-1 | | x^2+10=-16 |